Enhanced solar absorption and visible-light photocatalytic and photoelectrochemical properties of aluminium-reduced BaTiO3 nanoparticles. Issue 7 (23rd November 2017) - Li, Jing; Zhang, Ganghua; Han, Shaofeng; Cao, Jianwu; Duan, Linhai; Zeng, Tao
Abstract : Al-reduction treatment is proved to be an excellent strategy to tune inert ferroelectric materials toward efficient photocatalysts. Abstract : Enhanced solar light absorption and photocatalytic and photoelectrochemical properties have been achieved in black BaTiO3 with a unique core/shell structure (crystalline BaTiO3 @amorphous BaTiO3− x ) using an Al-reduction method. This finding may open a new avenue to tune the inert ferroelectric materials toward excellent photocatalysts for advanced applications.